Pengembangan Bahan Ajar Tematik Berbasis Nilai-Nilai Keislaman Kelas VI Madrasah Ibtidaiyah - Sumining, Sumining (EDUCARE: Journal of Primary Education, 2021)
Development of thematic teaching materials based on Islamic values, especially those related to the contents of the verses of the Alqur'an and / or hadith as the basis of all science. In the available books, there are no thematic teaching materials that are integrated with the Al-Quran and Hadith, as well as Islamic values ??that are able to implement the core competencies of the 2013 curriculum, namely the competence of spiritual attitudes in thematic learning. The formulation of this research is: (1) producing thematic teaching materials based on Islamic values ??theme 7 (Leadership) class 6 Madrasah Ibtidaiyah Negeri 2 Jember. (2) to determine the effectiveness of thematic teaching materials based on Islamic values ??in learning. This study uses a research and development research type, the Borg and Gall model which is divided into 10 steps, namely: (1) research and data collection (2) planning, (3) product draft development, (4) initial field trials, ( 5) revising the results of trials, (6) field trials, (7) improving products from field tests, (8) conducting field trials, (9) improving product results, and (10) disseminating and implementing. The testing technique was carried out by comparing the pre-test and post-test values. The data was calculated using the t-test and processed using the SPSS application to determine the effectiveness of teaching materials. The results of this study indicate: the validation test produces an average of 88.79% with the criteria that the book is very suitable for use in learning. In terms of attractiveness, this book is very interesting to use for students, this is based on the results of the questionnaire data given to students with an average of 88.24% with very attractive qualifications. Meanwhile, from the results of the pre-test and post-test based on the t count which shows that it is greater than the t table, it means that the book is effective for use in learning. Keywords: Teaching Materials; Thematic Learning; Islamic Value Pengembangan bahan ajar tematik berbasis nilai keislaman, terutama yang terkait dengan isi ayat Alqur'an dan/atau hadits sebagai dasar dari semua sains. Dalam buku yang telah tersedia tidak ada bahan ajar tematik yang terintegrasi dengan Al-Quran, dan Hadits, serta nilai-nilai Islam yang mampu mengimplementasikan kompetensi inti dari kurikulum 2013 yaitu kompetensi sikap spiritual dalam pembelajaran tematik. Perumusan penelitian ini yaitu: (1) menghasilkan bahan ajar tematik berbasis nilai keislaman tema 7 (Kepemimpinan) kelas 6 Madrasah Ibtidaiyah Negeri 2 Jember. (2) mengetahui efektifitas bahan ajar tematik berbasis nilai-nilai keislaman dalam pembelajaran. Penelitian ini menggunakan jenis penelitian pengembangan Research and Development, model Borg and Gall yang terbagi menjadi 10 langkah, yaitu: (1) penelitian dan pengumpulan data (2) perencanaan, (3) pengembangan draf produk, (4) uji coba lapangan awal, (5) merevisi hasil uji coba, (6) uji coba lapangan, (7) penyempurnaan produk hasil uji lapangan, (8) uji pelaksanaan lapangan, (9) penyempurnaan produk hasil, dan (10) diseminasi dan implementasi. Teknik uji coba dilakukan dengan membandingkan nilai pre-test dan post-test. Data dihitung dengan uji-t dan diolah menggunakan aplikasi SPSS untuk mengetahui efektifitas bahan ajar. Hasil penelitian ini menunjukkan: uji validasi tersebut rata-rata menghasilkan 88,79 % dengan kriteria bahwa buku tersebut sangat layak untuk digunakan dalam pembelajaran. Dari segi kemenarikan, buku ini sangat menarik untuk digunakan pada siswa, hal ini berdasarkan dari hasil data angket yang diberikan kepada siswa dengan rata-rata 88,24% dengan kualifikasi sangat menarik. Sedangkan dari hasil pre-test dan pos-test berdasarkan uji t hitung yang menunjukan lebih besar dari t tabel, berarti buku tersebut efektif untuk digunakan dalam pembelajaran. Kata Kunci: Bahan Ajar; Pembelajaran Tematik; Nilai Keislaman